Prevalence of Dermatophytosis among Children of Nomadic Herdsmen within Sokoto metropolis, Sokoto State, Nigeria - Shinkafi, S.A. * Muhammad, A. D. and Mohammed, N. (Sokoto Journal of Medical Laboratory Science)
Dermatophytic infections are a worldwide public health problem. In Nigeria, children of nomadic herdsmen are thought to be more at risk of this infection because of their early and continuous exposure to different kinds of animals. However, little is known about the level of infection in these children within Sokoto metropolis. This study was designed to investigate the incidence of dermatophytosis among children of nomadic herdsmen within Sokoto metropolis. To investigate the distribution of this infection based on different age groups, gender and sites of the body affected. A total number of thirty (30) children were investigated, aged between 0-20 years and with clinically suggestive lesions. Isolates were identified using microscopy and culture to identify isolates with typical morphology. Three categories of fungi were identified, these include; Yeasts, Moulds and Dermatophytes. The target organisms were dermatophytes and the species identified include; Trichophyton rubrum, Trichophyton schoenleinii and Trichophyton verrucossum. The result indicated that among the target organisms, Trichophyton rubrum was the most frequent organism isolated with the percentage frequency of occurrence of 8.16%, followed by Trichophyton verrucosum (6.12%) and the least was Trichophyton schoeleinii with the percentage frequency of occurrence of 2.04%. T. rubrum, T. verrucosum and T. schoeleinii which were the target organisms were found to be less prevalent species isolated in this study (16.30%), while the non-dermatophyte (yeast and moulds) were the most prevalent species with frequency of occurrence of 83.66%. The result shows that dermatophytic infections are prevalent among the poor than the rich. The results also indicated that dermatophytosis is more prevalent among children between ages of ≤11 years.  The results of this research show that dermatophytosis is more prevalent among female than male.